Pengaruh Kepemimpinan Kepala Madrasah dan Disiplin Guru terhadap Profesionalitas Guru di Madrasah Tsanawiyah Negeri Kota Jambi - Ermailis Ermailis; Raudhoh Raudhoh; Risnita Risnita (Postgraduate Studies UIN Sulthan Thaha Saifuddin Jambi, 2018)
The influence of Madrasah principals' leadership and teacher discipline on the professionalism of teachers in the Public Islamic Junior High School or Madrasah Tsanawiyah Negeri in Jambi City has been carried out in this research using a quantitative approach. This study aims to analyze the influence of the principal's leadership and teacher discipline on the professionalism of teachers and the influence of the combination of both. Data was collected using a survey method with 63 respondents who were distributed to Sijenjeng Madrasah as many as 24 people, while in Talang Bakung Madrasah there were 39 people. Based on the results of this study, it is found that the better the headmaster's leadership accompanied by the discipline of a teacher will affect the better formation of teacher professionalism with value of the influence of the headmaster's leadership (83.72%), teacher discipline (22.15%), and combination of leadership of the madrasah-discipline teacher (17.2%).